Molla Mousa Hakkari’s Durru’l-Mecalis and Its Importance in the History of Kurdish Folklore Studies - PERTEV, Ramazan (Humanities Journal of University of Zakho, 2022)
This article focuses on the Kurdish scholar Mullah Mousa Hekarî’s work called Durru’l-Mecalis and tries to explain it from various aspects. Since the 18th century, many Kurdish folklore materials have been compiled by foreign researchers. Among these, there are many works related to Kurdish folklore, especially in the collection of Auguste Aleksandre Jaba. For example, the works of Mullah Mahmoud Bazîdî are among the main works of this archive. This collection also includes Mullah Mousa Hekarî’s work called Durru’l-Mecalis, which has not been mentioned much until today. Since this work, which consists of 58 stories, was written in the 1600s, it can be considered as the first examples of Kurdish/Kurmandji prose. Some of these stories, such as “Farhad and Shirin” (23rd story) and “Dahhak” (36th story), in which folkloric elements are clearly seen, are very precious and original. According to the information in Evliya Çelebi’s Seyahatname (Travel Book), Mullah Mousa Hekari lived between the 16th and 17th centuries and he is one of the known scholars of Hakkari. He had translated many stories/folk tales from various sources, primarily Persian, into Kurdish. Mullah Mousa’s stories have two functions : pedagogical purpose and entertainment purpose. In other words, he wanted to give messages to his society through these stories according to the values, morals and aesthetic criteria of his age and to şow them the right attitudes and behaviors in the face of situations they may encounter in daily life. On the other hand, these stories have the function of having a good time in night conversations and entertaining. The themes of the stories are good and evil, arrogance and humility, justice and injustice, generosity and greed, love and loyalty, truth and betrayal, wealth and poverty, heroism and cowardice, help and solidarity, social humor, men and women, lives of prophets. In this article, we will examine the folkloric and linguistic features of the stories in Durru’l-Mecalîs in terms of form and content and, we will mention their importance in the history of Kurdish folklore studies.